P670 Therapeutic efficacy and economic impact of half sulfasalazine therapy for refractory ulcerative colitis. (25th January 2019) - Kunisaki, R; Tatsuno, M; Kouyama, J; Kawamoto, C; Nishioka, H; Mizoguchi, A; Nakamori, Y; Mitsui, T; Chida, K; Hashimoto, Y; Tamura, Y; Ikeda, A; et al.
Abstract: Background: Numerous novel biologics are emerging for refractory ulcerative colitis (UC), but rising medical costs are a serious problem. Sulfasalazine (SASP) is an inexpensive drug. Although the effectiveness of 5-aminosalicylic acid (5-ASA) and SASP for UC is equivalent, SASP sometimes appears effective for refractory UC in daily clinical practice. SASP has dose-dependent side effects and there is a considerable amount of cases of high-dose intolerance of SASP. To solve this problem, we have provided 'half SASP therapy' for patients with UC, where 5-ASA and SASP are administered in combination with half of a high dose. This study aimed to investigate the short- and long-term efficacy, safety, and economic effect of half SASP therapy in refractory UC. Methods: We performed a retrospective, observational study in two-IBD specialised facilities. We reviewed the outcome of patients with refractory UC who were treated with half SASP therapy from 2011 to 2018. Clinical remission and response were evaluated on the basis of the partial Mayo score. The cumulative rates of immunomodulator-, biologic- and colectomy-free survival rates were calculated using the Kaplan–Meier method. For evaluation of safety, any adverse event (AE) that occurred after administration of SASP was considered. Medication costs before and after treatment were also evaluated. Results: A total of 211 patients were enrolled. Among these, 52% had chronic active colitis with high-dose oral 5-ASA treatment and concomitant topical treatments, 48% were steroid refractory/dependent cases, and the median partial Mayo score was 5.0 (0–8). At Weeks 8, 26, and 52 after half SASP therapy, 26%, 35%, and 39% of the patients achieved clinical remission, respectively. Among 173 patients who continued therapy after a median follow-up of 3.0 years (0.3–7.3 years), immunomodulator-free survival rates at 1 and 5 years were 93% and 81%, respectively. The biologic-free survival rates were 95% and 84%, and colectomy-free survival rates were 99% and 91%, respectively. The AE rate was 37%, 17% of patients had to discontinue SASP, and five required hospitalisation for allergies. No other severe AEs or mortality occurred. The average medication cost before half SASP was 398 USD per month. At 52 weeks after treatment, medication costs were as follows: 52-week responder, 139 USD; discontinuation of SASP due to AEs, 401 USD; and 52-week non-responder, 953 USD per month. Conclusions: The incidence of AEs in half SASP therapy for refractory UC was high and 17% of patients needed to discontinue treatment, but there were no serious AEs. In patients who could continue therapy, the response rate was 60%, there was a good long-term prognosis, and medical costs were reduced.